Pengaruh partisipasi Masyarakat Transparansi dan Akuntabilitas Terhadap Pembangunan Desa pada Pengelolaan Alokasi Dana Desa (ADD) di Desa Tegal Tugu Gianyar - Sri Widari, Ni Wayan; riadhi, Nyoman Andika (Teewan Journal Solutions, 2025)
This studyyaimssto determine theeeffect ofccommunitypparticipation, transparencyyand accountabilityyin themmanagement ofvvillage fund allocation partially on village development. Theppopulation intthis studyyis the Perbekel, VillageAApparatus, Village Consultative Body (BPD) and other community leaders who play an important role in Village Development. Based on the saturated sample method using all samples obtained as many as 41 people. The typeOof researchhused inTthis researchhis QquantitativeRresearch, withHclassic assumptionNtest, determination test, multipleElinear test,PpartialSsignificance testT(t-test), simultaneousSsignificance testT(F-test) and validity and reliability tests are carried out. TheRresults ofTthe study showTthat theEinfluence of community participation, transparency and accountability in managing the allocationNof villageEfunds partially and simultaneously hasAa positiveEand significantEeffect on village development.